Karakterisasi Kandungan Fitokimia Estrak Daun Karamunting (Melastoma malabatchricum L.) Menggunakan Metode Gas Chromatography Mass Spectrometry (GC-MS) - , Muhammad Adiwena, Kartina,Mohammad Wahyu Agang (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2019)
Melastoma malabatchricum L. is a type of plant that is widely grown in South and Southeast Asia, including Indonesia and it has benefits as a medicinal plant. In Kalimantan, Karamunting leaves is used to treat wounds, fever, diarrhea, and tannins in its root is used to darken teeth or eyebrows. The usage standard of this plant as an herbal medicine is still based on people's habits, so research needs to be done to find out how much phytochemical content is found in M. malabatchricum L. The priorknowledge of phytochemical M. malabatchricum L. becomes the basis for developing its potential as a plant medicineÂ  and its use in various fields. This research was conducted at the Agriculture Faculty Agrotechnology Laboratory, UBT. The research consisted of characterization of Karamunting plants, leaf extraction by maceration, and phytochemical content analysis with GCMS. The results showed that M. malabatchricum leaf extract contained phenol compounds of 36.32%, fatty acids (20.74%), terpenoids (9.13%), sterols (5.77%), alkaloids (4.8%), amino acids (3.5%), aldehyde (3.15%), alcohol (1.54%) and several other compounds. Some types of compounds found are known to have potential as antibacterial, antiviral, antioxidant, cytotoxic, anticoagulant, wound healing, antidiareous, antivenom and anti-inflammatory.